Comparison of barrel-shaped fixed bed drying for different ventilation methods by mathematic simulation - Jianchun Yan; Hai Wei; Zhaoyan You; Huichang Wu; Huanxiong Xie (Case Studies in Thermal Engineering, 2022)
Unsteady one-dimensional partial differential equations for heat and mass transfer in peanut drying are used in mathematical simulations to compare the drying performance of a barrel-shaped bed in three ventilation modes: bottom up, inside out and outside in. Results obtained using the finite difference scheme show that the mathematical simulation reliably predicts the drying process of peanuts, and that the drying delay of bottom-up ventilation is the most significant at the beginning of drying. This is because the drying enhancement afforded by the high average velocity of air along the ventilation direction is insufficient to offset the drying delay caused by the large ventilation thickness compared with that afforded by the inside-out and outside-in ventilation. Furthermore, as the air volume flow increases, the time consumption and moisture content difference decrease, whereas the productivity, energy consumption, and uniformity increase for all three ventilation modes, consistent with the classical ventilation drying law. Under the same air volume flow, the time and energy consumptions for the bottom-up ventilation are the lowest, followed by those for the outside-in and inside-out ventilation. The productivity afforded by the bottom-up ventilation is the highest, followed by that by the outside-in and inside-out ventilation. The outside-in ventilation indicates the least moisture content difference and the best drying uniformity. Meanwhile, the inside-out ventilation indicates the most significant moisture content difference and the worst drying uniformity.